ANALISIS YURIDIS PERLINDUNGAN KONSUMEN DALAM PERJANJIAN BAKU JUAL BELI ENERGI LISTRIK PLN - , Endratmo Agus Bandrianto, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In this thesis titled Juridic Analysis in Standard Agreement on Electricity Energy Trade at PLN in Consumer Protection, there is a research to know how far Consumer Protection guaranted in using PLN Electric energy. To reach the purpose of this thesis, this research will using librarry research method and field research. Library research held by verified some dokumen like a primary law materials, secondary law materials, and the other. Field research doing by observation, interview, and make some quisionaire for respondent, they are PLN customers and PLN officers who doing their job to serve consumer. The result of this research show that protection for consumer in Standard Agreement on Electricity Energy Trade as regulate in Article 1320 Code of Civil, about agreement validation is complete and Consumer Protection Act Number 9 years 1999 that use some principles and rule which have a consumer protection characteristic have done well for a sense of justice to a parties in agreement.